Redox integration of signaling and metabolism in a head and neck cancer model of radiation resistance using COSMRO - Ji, Zhiwei; Moore, Jade; Devarie-Baez, Nelmi O.; Lewis, Joshua; Wu, Hanzhi; Shukla, Kirtikar; Lopez, Elsa I. Silva; Vitvitsky, Victor; Key, Chia-Chi Chuang; Porosnicu, Mercedes; Kemp, Melissa L.; Banerjee, Ruma; et al. (Frontiers in Oncology, 2023)
Redox metabolism is increasingly investigated in cancer as driving regulator of tumor progression, response to therapies and long-term patients’ quality of life. Well-established cancer therapies, such as radiotherapy, either directly impact redox metabolism or have redox-dependent mechanisms of action defining their clinical efficacy. However, the ability to integrate redox information across signaling and metabolic networks to facilitate discovery and broader investigation of redox-regulated pathways in cancer remains a key unmet need limiting the advancement of new cancer therapies. To overcome this challenge, we developed a new constraint-based computational method (COSMro) and applied it to a Head and Neck Squamous Cell Cancer (HNSCC) model of radiation resistance. This novel integrative approach identified enhanced capacity for H2S production in radiation resistant cells and extracted a key relationship between intracellular redox state and cholesterol metabolism; experimental validation of this relationship highlights the importance of redox state in cellular metabolism and response to radiation.